Regional Depositional Model Of South Makassar Basin Depocenter, Makassar Strait, Based On Seismic Facies - Rahmadi Hidayat; Salahuddin Husein; Sugeng Sapto Surjono (Journal of Applied Geology, 2015)
South Makassar Basin Depocenter (SMBD) is located in Southern Makassar Strait which has petroleum potential by the presence of oil and gas indications within the area based on Airborne Laser Fluorescence survey. However, detail studies within this area are not developed well. One of the studies which can be utilized for further discoveries of oil and gas field in SMBD is a study of depositional model using seismic facies method to maximize limited seismic and well data. Interpretation of depositional model in Eocene (syn-rift phase) was varied from alluvial plain and alluvial fan complex, continued gradually to platform. In Oligocene time (post-rift phase), massive transgression caused a major deepening in entire SMBD where the depositional environment changed to basinal plain. In early Miocene – recent interval (syn-orogenic phase), SMBD was relatively in stable condition at basinal plain environment. Lower Tanjung Sequence will be the most prolific petroleum play in SMBD due to its adequate source rock, reservoir rock and seal rock as well. Keywords: South Makassar basin, depositional model, seismic facies